Electron-impact state-to-state cross sections and rate coefficients for X(v)⃗A(v′) excitation of LiH molecule. (2nd March 2020) - Celiberto, R; Janev, R K; Laricchiuta, A
Abstract: Electron-impact cross sections for the v → v ′ transitions between the vibrational levels of X 1 Σ + and A 1 Σ + electronic states of the LiH molecule, are calculated from threshold to 1000 eV by using the threshold-modified Massey–Mott approximation. The rate coefficients for the same transitions are also calculated in the range 0.1–1000 eV. Scaling relationships for both the v  −  v ′ cross section and v  −  v ′ rate coefficients are derived, allowing us to represent the calculated quantities in a compact analytic form.